Effect of dietary orange peel extract on physiological, biochemical, and metabolic responses of Japanese quail reared under low ambient temperature - Ciftci, Mehmet; Simsek, Ulku Gulcihan; Dalkilic, Bestami; Azman, Mehmet Ali; Yilmaz, Okkes; Iflazoglu Mutlu, Seda; Bahsi, Muammer (Tubitak Scientific & Technological Research Council Turkey, 2016)
The effects of dietary orange peel extract (OPE) supplementation on growth performance, carcass traits, serum biochemical parameters, antioxidant status of tissues, and fatty acid composition of breast meat in Japanese quails reared under low ambient temperature were investigated in the present study. A total of 108 quails of 15 days old were assigned to 3 groups with 3 replicates. Animals were fed with a corn/soy-based standard diet in the control group and a standard diet supplemented with either 100 or 200 ppm of OPE in the experimental groups (control, OPE-100, and OPE-200 groups, respectively). Room temperature was gradually lowered at night weekly from 14 degrees C to 8 degrees C to obtain chronic intermittent cold stress. OPE supplementation significantly increased live weight, live weight gain, and improved feed efficiency. OPE lowered triglyceride, total protein, glucose, total cholesterol, and uric acid levels in serum. The lowest malondialdehyde levels for liver and heart tissues were found in the OPE-100 group. Glutathione peroxidase activity and glutathione production in liver and heart tissues were found higher in the OPE groups. The lowest vitamin C levels for liver and heart tissues were observed in the control group. Feeding OPE resulted in increased accumulation of C20: omega-6, C22: omega-3, and total omega-3 fatty acids and decreased C18:0 level and total omega-6/omega-3 ratio. These results suggest that OPE supplementation has positive effects against cold stress.
Keywords: Antioxidant; cold stress; fatty acid; Japanese quail; orange peel extract